Social media use and adolescents’ well-being: A note on flourishing - Marciano, Laura; Viswanath, Kasisomayajula (Frontiers in Psychology, 2023)
Background: Several large-scale studies and reviews have reported both negative and positive associations of social media use with well-being, suggesting that the findings are more complex and need more nuanced study. Moreover, there is little or no exploration of how social media use in adolescence influences flourishing, a more all-encompassing construct beyond well-being, including six sub-domains (i.e., happiness, meaning and purpose, physical and mental health, character, close social relationships, and financial stability). This paper aims to fill this gap by understanding how adolescents might flourish through social media activities by fulfilling the basic needs pointed out by the Self-Determination Theory, i.e., relatedness, autonomy, and competence. Methods: The study is drawn on cross-sectional data collected from 1429 Swiss adolescents (58.8% females, Mage=15.84, SDage=.83) as part of the HappyB project in Spring 2022. Self-reported measures included the Harvard Adolescent Flourishing scale, positive and negative online social experiences, self-disclosure on social media, and social media inspiration. Control variables included, among others, self-esteem, ill-being, and personality. Results: After applying Bonferroni’s correction, results of the hierarchical regression analyses showed that positive social media experiences (β=.112, p<.001) and social media inspirations from others (β=.072, p<.001) and for others (β=.060, p=.003) were positively associated with flourishing. Flourishing was inversely associated with negative social media experiences (β=-.076, p<.001). Among covariates, self-esteem (β=.350, p<.001), ill-being (β=-.252, p<.001), perceived school environment (β= .138, p<.001), self-reported level of physical activity (β =.109, p<.001), and perceived socio-economic status (β=-.059, p=.001) were all related to flourishing. In contrast, gender, high school year, age, perceived stress, and personality (extraversion and neuroticism) were not. Conclusion: Using a well-being framework to investigate social media use in adolescents is needed to go beyond the ill-being perspective. Our results align with the needs pointed out by the Self-Determination Theory. Carrying out social media activities in a way that promotes - rather than diminishes - flourishing should be included as an additional good habit influencing adolescents’ development. We suggest that interventions aiming to foster adolescents’ flourishing should include curricula aiming to promote a good use of social media through positive online social relationships and inspirational contents.